2022
DOI: 10.1002/adfm.202113030
|View full text |Cite
|
Sign up to set email alerts
|

CaV6O16·2.8H2O with Ca2+ Pillar and Water Lubrication as a High‐Rate and Long‐Life Cathode Material for Ca‐Ion Batteries

Abstract: Due to the low cost and low redox potential of calcium, calcium ion batteries (CIBs) are considered a competitive candidate for large‐scale energy storage systems and have attracted increasing attention in recent years. However, the development of CIBs is still in its infancy and hindered by the lack of high‐performance cathode materials. Herein, the metahewettite layered vanadium oxide with the Ca2+ pillar and water lubrication is reported as a cathode material for CIBs. Benefiting from the large interlayer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Compared with the original sample, the cycled VOPO 4 ·2H 2 O displays a discernible (001) peak right shift, which is due to the escape of the water or the irreversible insertion of Al 3+ . [ 20 ] Therefore, the TGA was conducted to figure out the water contents before and after cycling. As displayed in Figure 2e, it can be clearly observed for the decreased water content in the cycled VOPO 4 ·2H 2 O, corroborating the water escape during cycling.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the original sample, the cycled VOPO 4 ·2H 2 O displays a discernible (001) peak right shift, which is due to the escape of the water or the irreversible insertion of Al 3+ . [ 20 ] Therefore, the TGA was conducted to figure out the water contents before and after cycling. As displayed in Figure 2e, it can be clearly observed for the decreased water content in the cycled VOPO 4 ·2H 2 O, corroborating the water escape during cycling.…”
Section: Resultsmentioning
confidence: 99%
“…[26] Confining a certain amount of Al 3 + and H 2 O between the layers can expand the interlayer spacing of vanadium oxide and stabilize the layered structure. [27] For comparison, we synthesized and obtained the TEM and HRTEM images of pure V 6 O 13 , as shown in Figures S21 a and b (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Our group reported that Mg 0.25 V 2 O 5 ÁH 2 O with the pre-intercalation of Mg 2+ and H 2 O molecules 24 and CaV 6 O 16 Á3H 2 O with the pre-intercalation of Ca 2+ and H 2 O molecules. 25 The pre-intercalation of H 2 O molecules between the layers of V 2 O 5 can partially shield the electrostatically attractive forces between Ca 2+ and oxygen anions, leading to mild interaction and cycling stability. 24 However, Mg 0.25 26,27 Except for the pillar effect of H 2 O molecules, CVO possesses double electrochemical active sites enabled by M and V bimetallic redox, which is demonstrated in other electrochemical systems.…”
Section: Introductionmentioning
confidence: 99%